Essential Aspects in Digital Educational Games to Support the Teaching-Learning of Computing Contents - Zimbrão, Rafael De Oliveira; Oliveira, Alessandreia Marta De; Oliveira, Edmar Welington; Valle, Pedro Henrique Dias (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2024)
Context: Computer Science education mainly uses traditional strategies to teach students the content, which can cause discouragement in the learning process. To mitigate these problems, educational games have been used to support Computing Education. Problem: Educational games in the academic context have not been used in practice. Solution: This paper investigate the development of educational games to support computing education, looking for which characteristics present in educational games impact their longevity. IS Theory: This work was based on General Systems Theory, seeking to understand the development of educational games and how students interact with this software. Methodology: An SMS was carried out to achieve the goal of this paper. Summary of Results: 30 primary studies were analyzed. It can be concluded that for an educational game to have longevity, it is notable that it needs to be able to engage its users and have easy usability and features that promote good feedback for their students. Contributions and Impact in the IS area: The main contribution of this paper is to understand how educational games for Computing have been developed. In this sense, it gathers the necessary information for developing a quality and sustainable educational game, showing the benefits of a well-defined process to this software.